Selected Decisions (7th Ed). (Selected Decisions; Issue, Year, 1975)
This volume is the Seventh Issue of Selected Decisions of the IMF and Selected Documents. It contains the decisions, interpretations, and resolutions of the Executive Directors and the Board of Governors of the IMF to which frequent reference is made in the current activities of the Fund. In addition, the volume contains certain documents relating to the IMF and the United Nations. This issue contains most of the decisions that were published in earlier issues but not decisions that have ceased to be effective or that are referred to less frequently than in the past. A substantial part of this volume is devoted to decisions taken by the IMF since the last issue. With few exceptions, the decisions in this volume are general in application and relate to obligations, policies, or procedures under the Articles of Agreement. Subject to the few exceptions referred to, decisions that affect individual members are not included. Decisions of the Fund that are included in the By-Laws and the Rules and Regulations are general in application but are not reproduced in this volume.